Basic Obstetric Ultrasound Implementation and Maternal Trust: A Scoping Review - Kholidah, Miskiyatul; Jati, Sutopo Patria; Arso, Septo Pawelas (Syntax Literate, 2025)
Maternal trust in antenatal care (ANC) influences visit adherence, acceptance of clinical recommendations, and the overall pregnancy experience. Basic obstetric ultrasonography (USG) is a core component of ANC. Objective: To map 2020–2024 evidence on the implementation of basic obstetric ultrasound and its effects on maternal trust and satisfaction. Methods: Scoping review following Arksey & O’Malley and Levac frameworks, reported with PRISMA-ScR. Searches were conducted in PubMed/PMC, Wiley/Elsevier, SpringerOpen, and curated Indonesian national journals (Google Scholar). Inclusion criteria: studies (2020–2024) on pregnant women/ANC providers with outcomes on trust, satisfaction, or knowledge–attitudes toward ultrasound. Results: Of 1,126 records, 912 remained after removing duplicates; 74 full texts were assessed, and 20 articles were included. Three themes emerged: (1) ultrasound increases perceived quality and reassurance, thereby strengthening trust; (2) operator capacity (including midwives) and communication of results shape trust—equivocal findings can provoke anxiety when communication is insufficient; (3) access to portable/handheld devices and rural services enhances acceptability and perceived reliability. Conclusion: Timely, competent, and well-communicated basic obstetric ultrasound can strengthen maternal trust in ANC. Programs should ensure operator competence, standardized result communication, and clear referral pathways.